Nellie Simmons Meier papers - Meier, Nellie Simmons, -1939.; Meier, Nellie Simmons, -1939.
Autographed original palm prints, autographed photographs, and character sketches of 135 notable individuals such as Susan B. Anthony, Walt Disney, Amelia Earhart, and Booker T. Washington. The palm prints were assembled for Meier's book, Lions' Paws, the Story of Famous Hands (1937).
Palmist; born Nellie Simmons.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Anthony, Susan B. -- 1820-1906.; Disney, Walt, -- 1901-1966.; Earhart, Amelia, -- 1897-1937.; Washington, Booker T., -- 1856-1915.; Palmistry; Palmists